The impact of health insurance on access to health care in Sudan / Isam Eldin Elnour Mohamed Baloul - Isam Eldin Elnour, Mohamed Baloul (2017)
Health insurance (HI) is a form of health financing that is acknowledged, theoretically and empirically, to be an optimum health finance alternative with the potential of promoting access to healthcare and offering financial protection to its subscribers. In line with this, Sudan established a National Health Insurance Fund (NHIF) in 1994 to mitigate the low utilisation of care. The implementation of NHIF raised a number of public concerns pertain to the impact of HI on access, the exclusion of the poor, and whether HI escalates total healthcare. To contribute local evidence regarding each of these vital questions was the main motive that drove this study. The main objective here was to assess the impact of HI on access to healthcare services in Sudan. In addition, it assessed other determinants of access to healthcare. This study employed data from the Sudan Health Utilisation and Expenditure Household Survey, 2009 (SHUEHS 2009), to answer its objectives. The national survey had been performed between January and December 2009 and covered approximately 75,500. Descriptive analyses, followed by binary or multinomial logistic regression analyses, were applied to identify factors that determined access to different types of healthcare services. The study revealed that among all 72,526 respondents, 9832 (13.5%) had reported having acute illnesses and 6,124 (62.3%) sought healthcare. 4,608 (6.4%) of all the respondents reported having chronic illness in the last four weeks prior to the survey. Among those participants, 2351 (51%) had sought healthcare while the rest did not. Affordability was cited as the main reason for not seeking care. 1776 (2.4%) of all respondents were hospitalised over the previous one year prior to the survey. The iv insured status was found to increase the chance of access to healthcare for all types of diseases compared to those without insurance. For acute diseases, the insured had a 31.6%, higher chance of obtaining care than the non-insured; OR 1.316 (95% CI; 1.198 1.446). For chronic diseases, the insured had a 38% higher chance of seeking care compared to the non-insured; OR of 1.38 (95% CI; 1.19-1.6). Even for inpatient care, the insured were 20% more likely to use inpatient services than the non-insured; OR 1.2 (95% CI; 1.07-1.35). With regards to the role of HI on utilisation of private care, this study found that insurance status was not a significant predictor of utilisation of private care for the outpatient service. However, HI increased the likelihood of using private hospitals by 40%; OR 1.4 (95% CI 1.12-1.99). Based on the SHUEHS 2009 data, it is evident that possessing HI was associated with enhanced access to healthcare for both inpatient and outpatient services. This study showed that insurance enrolment was higher among wealthy and the affluent regions and societal groups. The findings of this work support the expansion of the NHIF as a powerful tool for improving utilisation of healthcare services. Strategies should be developed to ensure enrolment of the poor when planning the expansion of HI in Sudan.